KINERJA SURFAKTAN METIL ESTER SULFONAT (MES) SEBAGAI OIL WELL STIMULATION AGENT AKIBAT PENGARUH SUHU, LAMA PEMANASAN, DAN KONSENTRASI ASAM (HCl) - Erliza Hambali, Ani Suryani, Agus Pratomo, Pudji Permadi, Hadi Purnomo dan Siti Mujdalipah (Department of Agroindustrial Technology, Bogor Agricultural University, 2006)
ABSTRACTSurfactant is a surface active agent that has an ability to reduce interfacial tension (IFT). This ability has been used in an enhanced oil recovery (EOR) process to increase oil well poductivity, particularly in chemical stimulation. Methyl ester sulfonate (MES) is an anionic surfactant that can be used to substitute a commercial surfactant for the EOR process. The parameters such as salinity, kind of rock, temperature, pressure, and carrier are important parameters that can influence performance of surfactant in reducing interfacial tension.The research of  = 5% and  = 1% that is based on temperature effect and time of heating showed that temperature increased interfacial tension value. The research of  = 5% and  = 1% that is based on temperature effect and acid concentration showed that temperature and acid concentration increased interfacial tension value. The IFT value is affected by temperature and acid concentration.Keywords : methyl ester sulfonate,interfacial tension, temperature, and acid